Legal Implications of Artificial Intelligence on Personal Data Protection in Indonesia: A Literature Analysis of UU Nomor 27 Tahun 2022 - Winda Nurul Annisa (Sains Global Indonesia (SGI), 2025)
The development of Artificial Intelligence (AI) in Indonesia has brought significant impacts on the economic, governmental, and legal sectors, particularly in the management of personal data. This study analyzes the legal implications of AI implementation on data protection based on UU No 27 Tahun 2022 concerning Personal Data Protection (PDP Law) using a normative juridical method and literature study. The findings indicate that although the PDP Law represents an important step in data protection, the regulation has not yet fully addressed AI-related challenges such as algorithmic bias, lack of transparency, and unclear legal accountability. Therefore, legal reforms are needed to be more adaptive, emphasizing transparency, accountability, and algorithmic fairness, as well as enhancing the capacity of public officials to ensure that AI utilization remains ethical and aligned with the values of Pancasila.